Peningkatan Skill Literasi Digital dan Teknologi untuk Mendukung Pengelolaan Pembelajaran Daring - Isroah, Isroah; Widayati, Ani; Wibawa, Eka Ary (Borneo Research and Education Center, 2024)
Learning during the COVID-19 pandemic is dominated by online learning, where teachers need digital and technological literacy skills. However, many digital and technological literacy skills teachers possess are not optimal. Whereas digital literacy skills and technological literacy are supporters of the successful implementation of online learning. Thus, the Community Service Program Team provides training to improve digital literacy skills and technology to support online learning management. The service activity was carried out from July 17, 2021, to August 7, 2021, involving 23 MGMP accounting teachers in Kulonprogo Regency. Overall, this activity went smoothly and successfully. This success was shown, among others: a) As many as 83% of participants were able to set up Google Classroom, utilize online learning media, and set up online quizzes; b) 94% of participants are able and skilled in identifying key information, managing information from various sources, evaluating digital information; c) 94% of participants are able and skilled to learn new technology, practice various applications, use technology effectively, and differentiate technology appropriately.